Genetic Control of Growth, Wood Density and Stem Characteristics of Pinus pinaster in Portugal - Aguiar,Alexandre (2003)
A Pinus pinaster Ait. progeny trial involving 46 open pollinated families was established at two locations in Portugal (Leiria and Escaroupim). Height, diameter, Pilodyn and stem characteristics (straightness, branch size and number of whorls) were assessed at age 5 and 12 and were used to estimate variance components, heritability, phenotypic and genetic correlations between traits. Estimates varied considerably between the two sites. However, this study indicates that the heritability for height followed the general pattern of increasing with the age of the trees. A strong and favourable genetic correlation between the stem form and branching was also found. Heritability of Pilodyn was very low, suggesting that measurements taken at age 12 were not a reliable measure of wood density, probably due to the high proportion of juvenile wood.